Three-dimensional temperature and stress field simulation with all-hexahedral element mesh in a high efficiency cooling structure for the fabrication of amorphous ribbons. (1st March 2022) - Chen, Li; Li, Yuluo; Shen, Ningning; Hui, Xidong
Abstract: Planar flow casting is an advanced technology to produce amorphous and nanocrystalline ribbons in electrical application. At present, the utilization rate of roller surface is generally under 20% in industrial production. This work reports a new cooling structure that is designed to produce ribbons width 65 mm with the utilization rate of roller surface up to 65%. The cooling structure is simulated with the software ANSYS by employing three-dimensional temperature and stress field mathematic model incorporating actual production conditions with all-hexahedral element mesh. It is shown that the liquid velocity is uniform with consistent distribution of convective heat transfer coefficient in width direction between cooling water and rotating roller. The thermal expansion difference in the new cooling structure is only 0.0042 mm at the ribbon edge. In this case, it is unnecessary to make the slit with an upward bend. The new cooling structure is expected to be applied for industrial production at an ideal level.